3D Bioprinting of Neural Tissues. Issue 15 (16th November 2020) - Cadena, Melissa; Ning, Liqun; King, Alexia; Hwang, Boeun; Jin, Linqi; Serpooshan, Vahid; Sloan, Steven A.
Abstract: The human nervous system is a remarkably complex physiological network that is inherently challenging to study because of obstacles to acquiring primary samples. Animal models offer powerful alternatives to study nervous system development, diseases, and regenerative processes, however, they are unable to address some species‐specific features of the human nervous system. In vitro models of the human nervous system have expanded in prevalence and sophistication, but still require further advances to better recapitulate microenvironmental and cellular features. The field of neural tissue engineering (TE) is rapidly adopting new technologies that enable scientists to precisely control in vitro culture conditions and to better model nervous system formation, function, and repair. 3D bioprinting is one of the major TE technologies that utilizes biocompatible hydrogels to create precisely patterned scaffolds, designed to enhance cellular responses. This review focuses on the applications of 3D bioprinting in the field of neural TE. Important design parameters are considered when bioprinting neural stem cells are discussed. The emergence of various bioprinted in vitro platforms are also reviewed for developmental and disease modeling and drug screening applications within the central and peripheral nervous systems, as well as their use as implants for in vivo regenerative therapies. Abstract : 3D bioprinting promises great potential for manufacturing complex neural tissue scaffolds with precise patterning of functional bioactive factors, including biomaterials, cells, and small molecules. This review discusses various bioprinting modalities and bioink compositions that are used for in vitro neural tissue modeling, drug screening, and in vivo regenerative applications.